Microsoft Visio 2010 step by step - Helmers, Scott A., 1951- (Step by step (Redmond, Wash.), 2011)
Teach yourself how to create professional-looking business and technical diagrams with Visio 2010 - one step at a time. With Step by Step, you get hands-on guidance for using vector graphics to visualize, analyze, and communicate complex information, systems, and processes --